Research Brief on ETI Workforce Studies - (:unkn) unknown (My University, 2016)
The University of Wisconsin-Milwaukee Employment and Training Institute provided technical assistance to the Milwaukee Area Workforce Investment Board (Employ Milwaukee), the City of Milwaukee, Milwaukee Area Technical College, Milwaukee Public Schools, NAACP, and nonprofits. Research and policy papers (1992-2016) detailed the demographics of low-income working families and identified the strengths, availability and training needs of the central city labor force.
Keywords: unemployment insurance; recession; job training; construction trades; apprenticeships; African Americans